Phytoplankton Communities in Rudrasagar Lake, Tripura (North-East India) – A Ramsar Site - Bharati, Huirem; Deshmukhe, Geetanjali; Das, Sanjay Kumar; Kandpal, Basant Kumar; Sahoo, Lopamudra; Bhusan, Shashi; Singh, Yumlembam Jackie (International Journal of Bio-resource and Stress Management, 2020)
Phytoplankton is the integral link of food webs in the transfer of energy to higher aquatic communities that can also act as biological indicators for evaluation of trophic status of an aquatic ecosystem. The present study was carried out during October (2017) to May (2019) to assess the phytoplankton diversity and abundance of Rudrasagar lake, the largest freshwater wetland of Tripura. A total of 35 phytoplankton genera belonging to four main groups viz., Chlorophyceae (18 genera), Bacillariophyceae (9 genera), Cyanophyceae (7 genera) and Euglenophyceae (1 genus) were observed during the study. Chlorophyceae dominated the phytoplankton quantitatively followed by Cyanophyceae, Bacillariophyceae and Euglenophyceae. The phytoplankton constituted 82.21 – 88.05 percent of the total plankton population during the study period. The average monthly phytoplankton abundance varied between 14229–25970 cells l-1. One way ANOVA revealed significant seasonal variation in the abundance of the phytoplankton groups. Maximum species richness was observed in pre-monsoon season. The phytoplankton communities of Rudrasagar lake showed high Shannon Weiner index (3.004–3.996) and high Pielou’s evenness index (0.939–0.986). High Shannon Weiner and Pielou’s indices indicated high phytoplankton diversity and even distribution of phytoplankton communities respectively. Abundance of different phytoplankton groups showed significant correlation with temperature, depth, transparency, pH, alkalinity and nutrient concentrations (nitrite, nitrate and phosphate). Knowledge about the phytoplankton communities of Rudrasagar lake in relation to its water quality parameters will help in planning possible options for management and optimum utilization of the lake’s resources.